INTERVENSI GIZI SPESIFIK DENGAN PENDAMPINGAN GIZI TERHADAP STATUS GIZI BALITA DI KABUPATEN BANDUNG PROVINSI JAWA BARAT - widi hastuti (Poltekkes Kemenkes Bandung, 2017)
Wasting and Stunting are the main problem spreaded in towns and villages. To address nutritional issues, it is required two intervention groups which are nutrition-specific interventions and nutrition-sensitive interventions. Nutrition-sensitive interventions are the effort to prevent and reduce directly nutritional problems , particularly in the first 1,000 days of life. Specific nutritional intervention activities are generally carried out by the health sector such as nutritional counseling, growth monitoring, feeding and curing . Meanwhile, nutrition-sensitive interventions are the effort to disrupt and decrease the nutritional problems indirectly in the form of various development activities of not health. The aim of this study is to compare the differences of nutritional status of <59-month children before and after given specific nutritional interventions along with nutritional assistance inBandung Regency of West Java. The research design used the quasy exsperiment with pretest – posttest questionnaire to compare the nutritional status of infants before and after the intervention. The thirty Samples were underweight toddlers (Weight / Height) and wasting risk. and lived in Margaasih research in the District of Bandung regency, West Java province. The study was conducted from March to September 2016. The data was collected the characteristics of subjects, nutritional status (weight/height), the nutritional knowledge of mothers, feeding knowledge, knowledge of the care of sick children and the nutritional hygiene knowledge. the skewness test was used to analyse that the data was normally distributed. Sample characteristics data were presented in the form of a frequency distribution table and analyzed descriptively. Data nutritional status (weight/height), the nutritional knowledge of mothers, knowledge of feeding, knowledge of the care of sick children and knowledge of self hygiene were analyzed using bivariate dependent t-test statistic for comparing the difference before and after an intervention with a confidence level of 95% with ap-value < 0.05. The results of the study showed that there is a significant difference in nutritional status (weight / height) (P = 0.001), nutritional knowledge of mothers (P = 0.001), knowledge of feeding (P = 0.015), and knowledge of personal hygiene (P = 0.000), while knowledge of the care of sick children there is no difference in (P = 0.594). Result of multivariate test indicates the variables of the sick child care knowledge was a confounding factor affectingnutritional status value (weight / height). Nutritional assistance activities should be carried out regularly and sustainablyto initiate efforts for nutritional improvement as the main goal.